Benchmarking the Colombian Foresight Programme against practices in Europe and South America - Popper, Rafael; Keenan, Michael; Medina, Javier; Miles, Ian (Cuadernos de Administración, 2008)
Considering the growing importance of comparing foresight styles, this paper puts the Colombian Technology Foresight Programme (CTFP) practices into an international perspective. Here we benchmark the Programme against foresight activities in Europe and South America. This required the combination ofinformation from two foresight databases (built by the EFMN and SELF-RULE networks) which is based on a sample of 675 foresight exercises. A total of 32 studies conducted or supported by CTFP were benchmarked against practices in four regions where CTFP built project linkages: Northwest   Europe, Southern Europe, Eastem Europe and South America. North America was not included given that only a few events involved US practitioners and these were mainly linked to the capacity building activities on horizon scanning tools and techniques. Of course, simplistic benchmarking, that matches each feature of the Programme against similar features in other countries, is not enough to draw conclusions about the complexity of activities that have been pursued to the specific objectives of the Programme. However, benchmarking has proven to be a good instrument to stimulate the performance of key foresight indicators and to leam from experiences of others and thereby acquiring practical knowledge about current practices.